2018
DOI: 10.2147/ott.s174846
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RNF6 inhibits gastric cancer cell growth by suppressing STAT3 signaling

Abstract: Background and objectiveRNF6, an E3 ligase, has been reported to play an important role in the tumorigenesis in several tissues, but its role in gastric cancer is still unknown. In this study, we aimed to investigate the biological function and molecular mechanisms of RNF6 in gastric cancer.Materials and methodsThe expression levels of RNF6 were detected by quantitative real-time PCR (qRT-PCR) and immunoblotting in gastric cancer tissues and cell lines. Cell Counting Kit-8 assay was performed to evaluate cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…We established a protein-protein interaction (PPI) network consisting of 165 nodes and 170 edges and identified 18 hub genes by MCODE plugin in Cytoscape. The 18 hub genes have been reported to be associated with gastric cancer, which are CCND2 [27] STAT3 [28], TP53 [29], MCL1 [30], MYC [31], FOXO1 [32], FOXO3 [33], BCL2L11 [34], GSK3B [35], CDKN1A [36], CDH1 [37], PTEN [38], MTOR [39], MAPK1 [40], CASP3, CDC42[41], SMAD4 [42] and IL6 [43]. All of them were predicted target genes for hsa-miR-197-3p, hsa-miR-451a, hsa-miR-136-5p, hsa-miR-337-3p, hsa-miR-654-3p, hsa-miR-182-5p, hsa-miR-1228-3p, hsa-miR-942-5p, hsa-miR-488-3p and hsa-miR-876-3p, and all these 10 miRNAs were predicted miRNAs for hsa_circ_0001013.…”
Section: Discussionmentioning
confidence: 99%
“…We established a protein-protein interaction (PPI) network consisting of 165 nodes and 170 edges and identified 18 hub genes by MCODE plugin in Cytoscape. The 18 hub genes have been reported to be associated with gastric cancer, which are CCND2 [27] STAT3 [28], TP53 [29], MCL1 [30], MYC [31], FOXO1 [32], FOXO3 [33], BCL2L11 [34], GSK3B [35], CDKN1A [36], CDH1 [37], PTEN [38], MTOR [39], MAPK1 [40], CASP3, CDC42[41], SMAD4 [42] and IL6 [43]. All of them were predicted target genes for hsa-miR-197-3p, hsa-miR-451a, hsa-miR-136-5p, hsa-miR-337-3p, hsa-miR-654-3p, hsa-miR-182-5p, hsa-miR-1228-3p, hsa-miR-942-5p, hsa-miR-488-3p and hsa-miR-876-3p, and all these 10 miRNAs were predicted miRNAs for hsa_circ_0001013.…”
Section: Discussionmentioning
confidence: 99%
“…8 SHP-1 was also reported to be ubiquitinated and degraded into 26S proteasome, and the ubiquitin ligase RNF6 could activate STAT3 signaling by modulating SHP-1 ubiquitination in gastric cancer and colorectal cancer. 9,10 In the current study, ellagic acid (EA) was found to exert its antitumor activity by suppressing STAT3 in ESCC cells. In mechanism, EA could inhibit the expression of RNF6 and then stabilize SHP-1 in ESCC cells.…”
Section: Introductionmentioning
confidence: 85%
“…The human USP44 gene was generated and cloned into pcDNA3.1 vector with a Myc tag as previously described . The primers used for gene amplification were as follows: USP44, forward 5′‐ ATGCTAGCAATGGATACGTGCAAAC ‐3′, reverse 5′‐ TCAGCTAAGGATTTCATTAGACGAG −3′.…”
Section: Methodsmentioning
confidence: 99%
“…The human USP44 gene was generated and cloned into pcDNA3.1 vector with a Myc tag as previously described. 17 The primers used for gene amplification were as follows: USP44, forward 5 0 -ATGCTA GCAATGGATACGTGCAAAC -3 0 , reverse 5 0 -TCAGCTAAGGATTTCA TTAGACGAG −3 0 . Plasmids were transiently transfected into NSCLC or HEK293T cells by Lipofectamine 2000 (Invitrogen) according to the manufacturer's instruction.…”
Section: Plasmids Construction and Gene Transfectionmentioning
confidence: 99%